2022
DOI: 10.1186/s13018-021-02901-9
|View full text |Cite
|
Sign up to set email alerts
|

SLAMF6 is associated with the susceptibility and severity of rheumatoid arthritis in the Chinese population

Abstract: Objectives A recently published genome-wide association study identified six novel loci associated with rheumatoid arthritis (RA) in Korean population. We aimed to investigate whether these newly reported RA-risk loci are associated with RA in the Chinese population and to further characterize the functional role of the susceptible gene. Methods The susceptible variants of RA were genotyped in 600 RA patients and 800 healthy controls, including rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The single immunoglobulin IL-1-related receptor (SIGIRR) mRNA expression was decreased in the PBMCs of RA patients in a study including 79 such patients, and SIGIRR dysregulation might be related to RA pathogenesis and susceptibility ( 69 ). In a recently published study of 650 patients with RA, signaling lymphocyte activation molecule family 6 (SLAMF6) expression in the synovial tissue was 1.6-fold higher than in the controls and correlated with the severity and susceptibility of RA ( 70 ). An analysis showed that mRNA expression of the inflammasome genes NOD-like receptor family pyrin domain containing 3 ( NLRP3 ) and caspase recruitment domain-containing protein 8 ( CARD8 ) in the PBMCs of 230 RA patients from two different populations was correlated with susceptibility and RA progression ( p = 0.044) and with severity ( p = 0.03), respectively; in addition, the NLRP3 expression levels were also significantly elevated ( 71 ).…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%
“…The single immunoglobulin IL-1-related receptor (SIGIRR) mRNA expression was decreased in the PBMCs of RA patients in a study including 79 such patients, and SIGIRR dysregulation might be related to RA pathogenesis and susceptibility ( 69 ). In a recently published study of 650 patients with RA, signaling lymphocyte activation molecule family 6 (SLAMF6) expression in the synovial tissue was 1.6-fold higher than in the controls and correlated with the severity and susceptibility of RA ( 70 ). An analysis showed that mRNA expression of the inflammasome genes NOD-like receptor family pyrin domain containing 3 ( NLRP3 ) and caspase recruitment domain-containing protein 8 ( CARD8 ) in the PBMCs of 230 RA patients from two different populations was correlated with susceptibility and RA progression ( p = 0.044) and with severity ( p = 0.03), respectively; in addition, the NLRP3 expression levels were also significantly elevated ( 71 ).…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%
“…Which underscored the importance of the immune system as well as non-immune tissues for the development of RA (Kwon et al, 2020). Xia et al (2022) analyzed the expression of Frontiers in Pharmacology frontiersin.org SLAMF6 gene in synovial tissue of RA patients and in the control group. The expression of SLAMF6 was significantly higher in RA patients than that in the control group.…”
Section: Slamf2-and Slamf4-mediated Inflammation In Ramentioning
confidence: 99%
“…2b-d). Then 25 different cell clusters were grouped into seven cell types including T cells (0, 1,4,5,8,11,12,16,20), NK cells (7), B cells (6, 10,18,19), monocytes (2,3,13,15,17), neutrophils (9,21,23), megakaryocytes (14), and DC cells (22,24) by using UMAP clustering analysis (Fig. 2a).…”
Section: Single Cell Analysis Identi Es Abnormal Proportion Of Cells ...mentioning
confidence: 99%
“…Researchers have also identi ed a functional variant of SLAMF6 gene (rs148363003) that is associated with susceptibility to and severity of RA. Moreover, inhibition of the SLAMF6 signaling pathway has been shown to alleviate arthritis symptoms [20] . These results suggest that SLAMF6 plays an important role in the pathophysiological processes of RA and is considered a potential therapeutic target.…”
Section: Construction Of Subtype Classi Ers and Diagnosis Of Markersmentioning
confidence: 99%